Noncoding RNAs: Emerging Players in Muscular Dystrophies. (4th March 2014) - Falcone, Germana; Perfetti, Alessandra; Cardinali, Beatrice; Martelli, Fabio
Abstract : The fascinating world of noncoding RNAs has recently come to light, thanks to the development of powerful sequencing technologies, revealing a variety of RNA molecules playing important regulatory functions in most, if not all, cellular processes. Many noncoding RNAs have been implicated in regulatory networks that are determinant for skeletal muscle differentiation and disease. In this review, we outline the noncoding RNAs involved in physiological mechanisms of myogenesis and those that appear dysregulated in muscle dystrophies, also discussing their potential use as disease biomarkers and therapeutic targets.